Revision of the genus Palmanura Cassagnau, 1983 (Collembola: Neanuridae: Neanurinae: Sensillanurini) - Arango, Angela; Palacios-Vargas, José G.; Vázquez, Magdalena; Marín, Elida P. (Zootaxa, 2018)
A revision of Palmanura is presented, P. klompeni sp. nov. P. moralesi sp. nov., P. contrerasi sp. nov. and P. axelretanai sp. nov. are described and illustrated, and P. normae Palacios-Vargas, 1996 and P. sernai Palacios-Vargas & Simón Benito, 2009 are redescribed. New records and distribution data are given for several species and a key for identifying every species of the genus are included. A discussion on the ventral chaetotaxy of all genera of the tribe Sensillanurini and a comparison with other tribes of Neanurinae is also provided.